Acute neuronal injury : the role of excitotoxic programmed cell death mechanisms - Auer, Roland N. (Springer, 2010)
This book is the result of a convergence of scientific information regarding mechanisms that produce acute nerve cell death in the brain. Although seemingly disparate, stroke, brain and spinal cord trauma, coma from a low serum glucose concentration (hypoglycemia), and prolonged epileptic seizures have in common the inciting factor of excitotoxicity, the activation of a specific subtype of glutamate receptor by an elevated extracellular glutamate concentration that results in an excessive influx of calcium into nerve cells. The high calcium concentration in nerve cells activates several enzymes that are responsible for degradation of cytoplasmic proteins and cleavage of nuclear DNA, resulting in nerve cell death. The high calcium concentration also interferes with mitochondrial respiration, with the resultant production of free radicals that damage cellular membranes and nuclear DNA. Understanding the biochemical pathways that produce nerve cell death is the first step toward devising an effective neuroprotective strategy, the ultimate goal. Acute Neuronal Injury will be useful to neuroscientists and general cell biologists interested in cell death. The book will also be helpful to clinically oriented neuroscientists, including neurologists, neurosurgeons and psychiatrists.